Challenges to the Control of Breast Cancer in A Small Developing Country - Mungrue, Kameel (Libertas Academica, 2014)
OBJECTIVE: The aim of this study is to determine the clinicopathological features of breast cancer in two dedicated cancer treatment centers in north Trinidad. The histological types and stage at presentation were also investigated. DESIGN AND METHODS: A retrospective cohort design was used; data were collected from a review of medical records of patients meeting the entry criteria. Clinical and demographic data were extracted. RESULTS: A total of 640 patients were selected for the study and were available for the analysis. The annual cumulative incidence rate of breast cancer for the calendar years 2010 and 2011 in north Trinidad was 32.4 per 100,000 and 24.6 per 100,000 of the population. The age group between 51–60 years had the highest proportion of cases of breast cancer. There was a significant ethnic disparity in the occurrence of breast cancer, as it was more common in people of African origin than among South East Asians. Surgery and chemotherapy were the major interventions employed. CONCLUSION: Breast cancer prevalence continues to be high in Trinidad; we provide evidence of the extent of and the degree of sophistication required to care for patients with breast cancer in a health care system in a small developing country.